2016
DOI: 10.1111/tan.12840
|View full text |Cite
|
Sign up to set email alerts
|

Identification of five novel MHC class II alleles in cynomolgus macaques of Vietnamese origin

Abstract: We report here the identification of one Mafa-DPA1 and four Mafa-DQB1 novel alleles of Vietnamese cynomolgus macaques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Comparative study of DRB exon 2 in various Mafa populations confirmed that Mauritius and the Philippines have a restricted DRB polymorphism when compared to Vietnamese or Indonesian macaques [45]. The Vietnamese and Indonesian populations have a high diversity of DRB alleles [66,67]. Extensive interspecies DRB allele sharing was demonstrated by comparison with Macaca mulatta and Macaca nemestrina [49,68].…”
Section: Diversity Of Cynomolgus Macaque Populationsmentioning
confidence: 99%
“…Comparative study of DRB exon 2 in various Mafa populations confirmed that Mauritius and the Philippines have a restricted DRB polymorphism when compared to Vietnamese or Indonesian macaques [45]. The Vietnamese and Indonesian populations have a high diversity of DRB alleles [66,67]. Extensive interspecies DRB allele sharing was demonstrated by comparison with Macaca mulatta and Macaca nemestrina [49,68].…”
Section: Diversity Of Cynomolgus Macaque Populationsmentioning
confidence: 99%